Social Media in Urologic Healthcare: Transforming Treatment, Management, and Online Medical Communication - Jung Eun Yu; Jong Mok Park; Jung Yoon Kim (International Neurourology Journal)
Digital technologies and social media have fundamentally reshaped healthcare communication and the accessibility of medical information. This review examines the role of social media in urologic care, focusing particularly on its impact on treatment, management, and professional engagement. Patients commonly utilize social media to obtain health information, share experiences, and discuss treatment options, whereas healthcare professionals leverage these platforms for networking, education, and research dissemination. Despite these benefits, concerns persist about content credibility, inconsistent expert oversight, and disparities in social media usage across different demographic groups. While social media enhances patient engagement and expands access to medical information, its long-term effects on clinical outcomes and healthcare decision-making remain unclear. As digital health continues to evolve, ensuring content reliability through expert oversight and technological advancements will be crucial in optimizing the role of social media in urologic care.